Prediction of Psychosomatic Symptoms Based on an Invalidating Environment with the Mediating Role of Alexithymia in Individuals with Generalized Anxiety Disorder - Hajirahimkhan, Zeinab; Rahmani, Seifollah; Goudarzi, Mahmoud (Mental Health and Lifestyle Journal, 2026)
The aim of the present study was to predict psychosomatic symptoms based on an invalidating environment with the mediating role of alexithymia in individuals with generalized anxiety disorder. The research method was descriptive–correlational using a structural equation modeling design. A total of 300 individuals with generalized anxiety disorder who had referred to counseling centers in Tehran in 2025 were selected through convenience sampling and completed the Patient Health Questionnaire, the Toronto Alexithymia Scale, and the Childhood Invalidating Environment Scale. Data analysis was performed using structural equation modeling in SPSS 26 and AMOS 26. The findings indicated that the relationship between an invalidating environment and psychosomatic symptoms was positive and significant (β = 0.35, p < .01). In addition, alexithymia played a mediating role in the relationship between an invalidating environment and psychosomatic symptoms (β = 0.30, p < .01). Therefore, it can be concluded that an invalidating environment affects psychosomatic symptoms in individuals with generalized anxiety disorder both directly and indirectly through the mediating role of alexithymia. It is suggested that psychologists and therapists apply appropriate therapeutic interventions, including dialectical behavior therapy and emotional self-regulation training, to reduce alexithymia and, consequently, mitigate the impact of childhood invalidating environments on psychosomatic symptoms.